How do people talk decades later about their crisis that we call psychosis? A qualitative study of the personal meaning-making process. Issue 2 (3rd April 2019) - Bergström, Tomi; Seikkula, Jaakko; Holma, Juha; Mäki, Pirjo; Köngäs-Saviaro, Päivi; Alakare, Birgitta
ABSTRACT: Psychosis refers to a severe mental state that often significantly affects the individual's life course. However, it remains unclear how people with the lived experiences themselves view these phenomena, as part of their life story. In order to evaluate this personal meaning-making process, we conducted in-depth life-story interviews with 20 people who had been diagnosed with non-affective psychosis 10 to 23 years previously in one catchment area. 35% of them were still receiving mental health treatment, and 55% of them were diagnosed with schizophrenia. Only a minority named their experiences as psychosis. On the basis of narrative analysis, two types of stories appeared to encompass how mental health crises and/or related experiences were presented as part of the life story: (i) crisis as a disruptor of the normative course of life ( N = 9), and (ii) crisis as an expected reaction to life adversities ( N = 7). In the majority of the stories, the mental health crisis was associated with cumulative life adversities in a central life area. Correspondingly, most of the factors that brought relief were narrated as inseparable from social and other real-life environments. We discuss the need for more person-centred and collaborative models of research and treatment.